Penamaan Semantis pada Kuliner Khas Tasikmalaya - Lisna Lestari; Ferani Siti Nurhanifah; Resti Sri Monika; Gita Wulansari; Aveny Septi Astriani (BADAN PENERBIT STIEPARI PRESS, 2024)
This study aims to examine and describe semantic analysis in typical Tasikmalaya culinary. This research is a qualitative descriptive research. Data were obtained using the literature study method and the listen method on naming typical Tasikmalaya culinary lexemes. The results showed that naming in typical Tasikmalaya culinary can be lexical, specific, contextual and non-differential.